Competitiveness of wheat (Triticum aestivum L.) genotypes against weed infestation under two different spacings in Sub-Himalayan plains of West Bengal - Hansda, Manmatha; Das, Saikat; Mitra, Biplab (Journal of Cereal Research, 2013)
Sub Himalayan plains of West Bengal has the characteristics of high rain fall and high humidity triggering aggressive growth of weeds which become one of the major constraints in crop production during rabi season. An experiment was carried out with three genotypes of wheat namely K0307, HD 2733 and DBW 39 to evaluate the competitiveness of these varieties against high weed pressure under two different spacings (15 cm and 20 cm). The dominant weed flora in the experimental field was two species of Polygonum having higher competitive ability and damaging potential than other broad leaved weeds. At 60 DAS the mean weed density of Polygonum were very high in weedy check comprising more than 85 per cent of the total weed population. Difference in weed density and weed fresh and dry weight was very low between 15 and 20 cm spacing. Successful control of weeds registered higher grain yield (39.70 q ha-1) against weedy check and yield reduction was found to the tune of 69.7% in weedy plots. Weed free plots also registered higher net return (Rs. 22870 ha-1) and B-C ratio (2.10) in comparison to non remunerative weedy check. Spacing had no significant effect on number of grains per spike or 1000 grain weight but net return and B-C ratio were slightly higher in 15 centimeter row spaced crop than 20 centimeter. Among the varieties, K0307 recorded significantly higher no. of tiller per sq. meter (298.5) as well as no. of grains per spike (43.2) resulting in increased yield performance (31.59 q ha-1). Similarly, maximum net return (Rs. 16249 ha-1) and B-C ratio (1.88) were also recorded with K0307 as compared to other two varieties.